Implementasi Kurikulum K13 pada Anak Berkebutuhan Khusus - Mochamad Ichsan Nur; Muhammad Ardy Zaini; Ismail Marzuki (Bidayatuna, 2022)
This study aims to find out the implementation of the 2013 Islamic Religious Education curriculum which is applied at the Special School for Muslim Cendekia, Tangerang Regency. The case study focuses more on the classification of mentally retarded and autistic children. This type of research is a qualitative field research with descriptive analysis. The research carried out only focuses on analyzing and providing an overview of the situation that occurs based on the actions and words of the sources interviewed or observed. This field research uses information obtained from informants or respondents through data collection instruments such as interviews, documentation, observation and data validity. The approach applied in this study is a psychological approach to behavioristic theory by analyzing the stimulus-response relationship. While the data analysis technique of this research uses four steps, namely, data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that: First, SKh Muslim Cendekia has implemented the 2013 PAI Curriculum but in practice modifications are made to certain things. Second, the implementation of the 2013 PAI Curriculum at SKh Muslim Cendekia still adheres to basic aspects such as planning, implementation, and assessment. However, the planning and implementation aspects were slightly modified. Third, the problems in implementing the 2013 PAI Curriculum at SKh Muslim Cendekia include PAI materials, the use of methods and media that have not been devoted to children with special needs, and the making of syllabus and lesson plans which are still an obstacle for teachers. The solution to overcome these problems is to build communication between the organizers in this case the Banten Province Special Education Office, Supervisors, Schools, and PAI Teachers to sit together. Keyword : Implementation, curriculum of 2013, children with special needs